Extreme Outliers in Lower Stratospheric Water Vapor Over North America Observed by MLS: Relation to Overshooting Convection Diagnosed From Colocated Aqua‐MODIS Data. Issue 24 (19th December 2020) - Werner, F.; Schwartz, M. J.; Livesey, N. J.; Read, W. G.; Santee, M. L.
Abstract: Convectively injected water vapor (H2 O) in the North American (NA) summer lowermost stratosphere results in significant outliers in the 100‐hPa H2 O measurements from the Aura Microwave Limb Sounder (MLS). MLS statistics from 15 years confirm that the NA region contains over 60% of global 100‐hPa H2 O > 12 ppmv, despite having only ∼1.8% of all MLS observations. A profile sampled in August 2019 stands out, with H 2 O = 26 . 3  ppmv, far exceeding the prior record and the median ∼4.5‐ppmv abundance in NA. This particular outlier is associated with a large overshooting convective event (OCE) that spanned multiple U.S. states and persisted for several hours. Colocation of the MLS data over NA with cloud observations from Aqua's Moderate Resolution Imaging Spectroradiometer (MODIS) reveals the unique character of this case, as only 2.3% of MLS profiles are as close to an OCE and only 0.024% of OCEs cover as large an area within a 500‐km perimeter of a profile. Plain Language Summary: Large‐scale convection over the North American continent during the summer can significantly moisten the lowermost stratosphere. This study provides statistical analysis of 15 years of humidity outliers observed from space, including a recent event that yielded an outlier that far exceeded typically observed background values and summer enhancements. It is shown that this sampled air mass was in close proximity to an exceptionally large and long‐lived convective event. Further analysis reveals that these two factors help explain the largest humidity outliers. Key Points: A profile with unprecedented stratospheric humidity is associated with large overshooting convection Large lower stratospheric humidity outliers are in close proximity to strong overshooting convection MLS humidity indicates trend toward larger stratospheric outliers and strengthening of North American monsoon